Postoperative pancreatic fistula - Hackert, Thilo; Werner, Jens; Büchler, Markus W. (The surgeon, 2011)
Postoperative pancreatic fistula is an important complication after pancreatic resection. The frequency of its incidence varies between 3% after pancreatic head resections and up to 30% following distal pancreatectomy. In recent years, the international definition of pancreatic fistula has been standardised according to the approach of the International Study Group on Pancreatic Fistula (ISGPF). Consequently, results from different studies have become comparable and the historically reported fistula rates can be evaluated more critically. The present review summarises the currently available data on incidence, risk factors, fistula-associated complications and management of postoperative pancreatic fistula.